ABOUT PROBLEMS AND SCIENTIFIC ACHIEVEMENTS OF RUSSIAN SCIENTISTS IN GRAIN AND OTHER CROPS - A. M. Medvedev; A. S. Vasyutin (Зерновое хозяйство России, 2018)
The results of studies of selection and seed-growing of  energy saturated crops including maize, soybean, winter wheat, winter triticale, sunflower, peas and rape (colza) made by some research institutions of RF are given. The state, effectiveness of researches, competitiveness of domestic cultivars and hybrids, possibilities of innovative use of new cultivars in production, problems constraining the development of scientific experiments are considered in the article. Special attention has been paid to domestic scientific achievements in selection of field crops. It has been emphasized that the best cultivars of winter wheat, winter triticale, selected in Krasnodar RIA, All-Russian RI of grain crops, Moscow  RIA “Nemchinovka” and in other RI are quite competitive with foreign cultivars and give yields of high qualitative grain (8-12 t/ha) when follow recommended scientifically approved technology of tillage. The same conclusions have been made in regard to maize, sunflower, soybean, peas and rape (colza). The necessity of optimal decision of urgent problems of seed-growing of perspective cultivars and hybrids; implementation of the best genotypes into production; use of sizing, disinfecting chemicals, fertilizers increasing growth energy and plant development before seeding have been considered in the article. It was noted that weakness of seed-growing logistical base, absence of modern plants and production lines for seed processing in research institutions and in seed-growing farms occupy a special place among the reasons constraining preparation of high qualitative seeds. It has been emphasized that mentioned circumstances negatively affect on competitiveness of domestic cultivars and hybrids on internal and foreign markets. In the article we suggested to strengthen participation of agrarian enterprises in solving the problems of development of modern seed-growing logistical base in Russia.